ACQUIRED β−THALASSEMIA IN CHILDREN WITH ACUTE LYMPHOBLASTIC LEUKEMIA (ALL) - Maria Christina Shanty Larasati; Mangihut Rumiris; Mia Ratwita Andarsini; I Dewa Gede Ugrasena; Bambang Permono (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2013)
Thalassemias are heterogeneous group of genetic disorders. β-thalassemia is existed due to impaired production of beta globins chains, which leads to a relative excess of alpha globin chains. The abnormalities of haemoglobin synthesis are usually inherited but may also arise as a secondary manifestation of another disease, most commonly haematological neoplasia. This article presenting two cases of acquired β-thalassemia in children with ALL focusing on the diagnosis and the possible relationship between the two haematological diseases. The first case is a four (4) year old boy with ALL-L1 type at maintenance phase of chemotherapy, he suffered from anaemia with Hb 8.0 g/dL, WBC 22,600/mm3 and platelets count of 200,000/mm3, peripheral blood smear revealed anisocytosis, polychromes, hypochromia, basophilic stippling, and normoblastocytes. The result of Hb electrophoresis of Hb A of 54.9%, Hb F of 29.4%, Hb E of 13.4% and Hb A2 of 2.3%. The patient was diagnosed as ALL-L1 type and β-thalassemia. The second case, is a 13 year old girl with remission ALL-L1 type after chemotherapy, she suffered from anaemia with Hb 6.7 g/dL, WBC 12,400/mm3, platelet count was 200,000/mm3, and peripheral blood smear obtained anisocytosis, hypochromia, normoblastocytes, myelocytes and basophilic stippling. The result of Hb electrophoresis are: Hb F 0.41%, Hb A1c 0.78%, Hb A2 2.95% with the conclusion of a β-thalassemia trait, this patient was diagnosed with ALL-L1 type remission + β-thalassemia trait. The case reviewers assume that acquired β-thalassemia which happened in those patients were the altered expression of globin chain which mechanism for this syndrome might be the acquisition of a mutation that affects RNA or proteins involved in β-globin gene regulation and resulting the reduction of the (α/β)-globin biosynthetic ratios, or/and associated with chemotherapy-inducement.